Comparison between the effects of aerobic and isometric exercises on primary dysmenorrhea - Elbandrawy, Asmaa M; Elhakk, Sahar M (Acta Gymnica, 2021)
Background: Primary dysmenorrhea is a cramping pain in the lower abdomen occurring just before or during menstruation without pelvic pathology. One of the methods used to decrease this condition's severity is exercise. Objective: The aim of this study was to compare the effects of aerobic and isometric exercises on primary dysmenorrhea. Methods: This was a randomized clinical trial that included 105 females aged 18-25 years complaining of primary dysmenorrhea. The participants were divided into three groups equal in number: (1) aerobic exercise (n = 35), (2) isometric exercise (n = 35), and (3) control group (n = 35). The two intervention groups performed exercises three times a week for eight weeks (two menstrual cycles). Participants were assessed using the plasma progesterone levels, visual analogue scale, and modified menstrual symptom questionnaire. Results: The within-group comparisons before and after the training program demonstrated significant differences in the aerobic exercise group regarding the visual analogue scale (p = .001, d = 0.652), plasma progesterone levels (p = .001, d = 0.688), and modified menstrual symptoms questionnaire (p = .001, d = 0.607). Also, there were significant differences in the isometric exercise group regarding the visual analogue scale (p = .001, d = 0.633), plasma progesterone levels (p = .001, d = 0.502), and modified menstrual symptoms questionnaire (p = .001, d = 0.462); however, no significant differences were observed in the control group. In addition, after the end of the exercise program when compared with their corresponding values measured before intervention significant differences were observed regarding these parameters between the aerobic and control group (p = .001) as well as between the isometric and control group (p = .001). On the other hand, after the end of the exercise program no significant differences were observed between the aerobic and isometric groups regarding the visual analogue scale (p = .14) or plasma progesterone level (p = .14); however, a significant difference was observed in the modified menstrual symptoms questionnaire between these two groups (p = .001) with favor to the aerobic exercise group. Conclusions: Both aerobic and isometric exercises are effective in reducing the severity of dysmenorrhea.
Keywords: dysmenorea; Young Adult; mladiství; Dysmenorrhea; Clinical Studies as Topic; klinická studie jako téma; lidé; Female; ženské pohlaví; cvičení; Humans; mladý dospělý; Exercise; Adolescent